Predictors of survival in pediatric intensive care unit in a low-income country: A retrospective cohort study - Mohamedawel Mohamedniguss Ebrahim; Abdikarin Ahmed Mohamed; Mohammed Mustefa Mohammedamin (PLoS ONE, 2025)
Background The goal of a pediatric intensive care unit is to treat life-threatening illnesses. Yet, there is a lack of data on survival rates and factors influencing survival in pediatric intensive care units (PICUs) in low-income countries like Ethiopia. Objective The purpose of this study was to evaluate survival and its predictors in the pediatric intensive care unit of Ayder Comprehensive Specialized Hospital, Tigray, Ethiopia. Method A retrospective cohort study was implemented on a total of 223 patients admitted to the PICU from September 2019 to August 2020. Using a checklist, trained healthcare workers gathered secondary data from patient charts. The dependent variable was time-to-death. EpiData 4.6 and STATA 16 were used for data entry and data analysis, respectively. Descriptive statistics, cumulative incidence, incidence density, median survival time, and adjusted hazard ratio were calculated to describe variables, estimate mortality rate and risk, and identify factors associated with survival. P<0.05 was used to declare a statistically significant relationship. Result A total of 46 (20.6%) deaths were recorded in this study. The cumulative incidence of death was higher in patients transferred from the ward to the intensive care unit (34.7%). The death rate was higher in patients with cardiac problems (40.0%), followed by oncological diseases (35.0%) and infectious diseases (27.9%). The adjusted risk of death was 3.3 times higher in pediatric patients with heart problems than in patients without heart problems. Again, the adjusted risk of death in children with a Glasgow Coma Scale (GCS) of 9 to 14 and a GCS below 9 was 2.2 and 2.5 times higher, respectively, than in children with a GCS of 15. Finally, children with endotracheal tubes were about five times more likely to die than children without endotracheal tubes. Conclusion It’s critical to diagnose and treat cardiac issues in pediatric patients as early as possible. Patients with low GCS scores require careful observation. Alternative strategies should be taken into consideration in order to lessen the need for endotracheal tubes and enhance results.